Dysregulated Urinary Arginine Metabolism in Older Adults With Amnestic Mild Cognitive Impairment - Zhang, Yue-qi; Tang, Ya-bin; Dammer, Eric; Liu, Jian-ren; Zhao, Yu-wu; Zhu, Liang; Ren, Ru-jing; Chen, Hong-zhuan; Wang, Gang; Cheng, Qi (Frontiers in Aging Neuroscience, 2019)
Background: Urine samples, which capture an individual’s metabolic profile, are ideal for the exploration of non-invasive biomarkers to confirm the amnestic mild cognitive impairment (aMCI) status of patients vs. unimpaired ones. Objective: We aimed to detect differentially metabolized amino acids, which are important objectives in metabolomics, garnering particular attention in biomedical pathogenesis from the urine of aMCI patients, which may give clinicians the possibility to intervene with early treatments that curb Alzheimer’s disease (AD). Methods: The study included 208 subjects, 98 of whom were aMCI patients, and 110 who were control subjects without dementia. Urine samples were taken from each participant and supernatant was obtained for analysis. The concentrations of amino acids were measured by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Results: Urinary arginine levels in aMCI patients are obviously lower than in normal controls (q < 0.2 and p < 0.05). Meanwhile, aMCI patients had significant reduced urinary global arginine bioavailability ratio (GABR), and GABR in urine displayed a positive correlation with the score of CMMSE. Conclusion: Urinary dysregulated arginine metabolism that may serve as a helpful clinical diagnostic biomarker for aMCI in older adults.